Case Report: Molecular Diagnosis of Fungal Keratitis Associated With Contact Lenses Caused by Fusarium solani - Trovato, Laura; Marino, Antonio; Pizzo, Giovanni; Oliveri, Salvatore (Frontiers in Medicine, 2021)
Fusarium is a filamentous fungus commonly found in the environment and is the major cause of fungal keratitis. We report a case of keratomycosis caused by Fusarium solani in a patient using disposable soft contact lenses. A delay in diagnosis led to the initiation of an empirical antifungal treatment with the subsequent deterioration of the patient’s clinical condition. The use of the real-time quantitative PCR assay confirmed keratitis from Fusarium solani providing a result in less than 48 h and therefore giving the possibility of quickly starting targeted antifungal therapy. The patient had an improvement in eye condition after the diagnosis of keratitis by Fusarium solani and the rapid change to targeted antifungal treatment. For the rapid identification of corneal fungal pathogens, we believe that PCR may be added for the diagnosis of mycotic keratitis pending the isolation in culture that is necessary for in vitro susceptibility testing.